Fisheries structure and management implications in Sundarbans mangrove reserve forest, Bangladesh - Hoq, M Enamul; Islam, M N; Kamal, M; Wahab, M A (Indian Journal of Fisheries, 2011)
Sundarbans mangrove forest of Bangladesh have been providing a wide array of fisheries activities for forest dependent communities and subsistence for coastal people. Penaeus monodon post larvae has emerged as one of the most important fisheries of the Sundarbans in terms of income, employment and contribution to the country’s export earning. At least 14 types of fishing gears are employed in Sundarbans, majority of which has a relatively high selectivity (mean number of major species caught <10). Dried fish industry in Sundarbans is a major economic activity compared to wood and non-wood products of the forest. Present indications are that there is almost non-existent management resulting in serious over-exploitation of all the fish stocks and requires immediate management attention.